Vaccine delivery to newly arrived refugees and estimated costs in selected U.S. clinics, 2015. Issue 20 (11th May 2018) - Pezzi, Clelia; McCulloch, Audrey; Joo, Heesoo; Cochran, Jennifer; Smock, Laura; Frerich, Ellen; Mamo, Blain; Urban, Kailey; Hughes, Stephen; Payton, Colleen; Scott, Kevin; Maskery, Brian; et al.
Highlights: Newly arrived refugees may have been vaccinated in the overseas vaccination program for US-bound refugees. All selected US clinics reviewed refugee overseas immunization records prior to vaccinating. Average vaccination costs and number of doses varied by state. Total average cost of US vaccination was less among refugees with overseas vaccinations. Abstract: Background: Newly arrived refugees are offered vaccinations during domestic medical examinations. Vaccination practices and costs for refugees have not been described with recent implementation of the overseas Vaccination Program for U.S.-bound Refugees (VPR). We describe refugee vaccination during the domestic medical examination and the estimated vaccination costs from the US government perspective in selected U.S. clinics. Methods: Site-specific vaccination processes and costs were collected from 16 clinics by refugee health partners in three states and one private academic institution. Vaccination costs were estimated from the U.S. Vaccines for Children Program and Medicaid reimbursement rates during fiscal year 2015. Results: All clinics reviewed overseas vaccination records before vaccinating, but all records were not transferred into state immunization systems. Average vaccination costs per refugee varied from 120 to 211 by site. The total average cost of domestic vaccination was 15% less among refugees arriving from VPR- vs. nonVPR-participating countries during a single domestic visit. Conclusion: Our findings indicate that immunization practices and costs vary between clinics, and that clinics adapted their vaccination practices to accommodate VPR doses, yielding potential cost savings.